Burmese grape fruit juice can trigger the "logic gate"-like colorimetric sensing behavior of Ag nanoparticles towards toxic metal ions1. Issue 30 (3rd April 2015) - Alam, Md Niharul; Chatterjee, Anirban; Das, Sreeparna; Batuta, Shaikh; Mandal, Debabrata; Begum, Naznin Ara
<x xml:space="preserve">Abstract</x> Ag NPs synthesized by Burmese grape fruit juice showed selective Hg2+sensing activity.